PENGARUH KERAGAMAN PRODUK TERHADAP KEPUASAN KONSUMEN PADA DEPOT MANDARIEN MOESLEM KABUPATEN SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Annisa R, Auliyah; Perwitasari W, Dwi; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is an activity that needs to be carried out by a company, be it a company of goods or services in an effort to maintain the survival of its business. Swasta and Handoko (2011:4) stated that